Microcomputers concepts, skills and applications - Flynn, Meredith (South-Western Publishing, 1998)
This book introduces current microcomputer applications being used in business today. It provides students with the opportunity to identify and understand the concepts related to all areas of microcomputer applications as well as the operational skills needed to use the application software. In addition to word processing, database management systems, and spreadsheets, there are chapters devoted to integrated software, desktop publishing, graphics, multimedia, virtual reality, telecommunications, networking, and the Internet. Areas of computer literacy including computer history, ethics, security, and examples of how computers are being used in both business specifically and society in general are also covered.